Comparative study of accounting students' performance: 'Do it First' and 'Cooperative Traditional Learning' approaches / Norlaila Abdullah - Abdullah, Norlaila (2006)
This study describes the academic and incremental performance of students by using two university alternative teaching techniques of Do It First (DIF) and Cooperative Traditionally Taught (CTG) approaches. Comparison of student's achievements in both methods is one of the many issues tested in this study to determine the more appropriate route to better learning. It further focuses on the level of preparation, likeness of courses, hours taken of outside class, quality of education, peer supports and friendliness and investment worthiness as moderating variables. This experimental study was conducted through the use of survey questionnaires to a cohort group of 30 students and the use of secondary data available in the university substantiates the rest of the research outcomes.